Copy number variants associated with epilepsy from gene expression microarrays. Issue 12 (December 2015) - Wang, Dong; Li, Xia; Jia, Shanshan; Wang, Yan; Wang, Zhijing; Song, Xixiao; Liu, Liang
Abstract: We aimed to identify novel copy number variations (CNV) that might contribute to the pathogenesis of epilepsy. Epilepsy is a common brain disorder characterized by recurring seizures and various serious comorbidities, including respiratory, cardiovascular, and neurologic dysfunction. CNV have recently been considered as important risk factors for epilepsy. With public gene expression data from brain tissue of 23 epilepsy patients and 23 healthy controls, we detected CNV using the R language package CAFÉ. Real-time quantitative polymerase chain reaction validation was performed in a further nine patients and 10 controls. Functional analyses of the genes in the validated CNV were also carried out, using Ingenuity pathway analysis. Three copy number abnormalities (19q13.33, 19q13.11 and 4q35.1) were detected with the gene expression data. The duplication in 19q13.33 (approximately 1.22 million bases) was further validated in three additional epilepsy patients, and the deletion in 19q13.11 (approximately 855 kilobases) was further validated in another two epilepsy patients. The functional analyses of the genes in these two CNV suggested that they may be involved in the pathogenesis of epilepsy. The CNV that we detected may be common genetic etiological factors of epilepsy, and there is potential for the identification of a novel biomarker for treatment from these CNV regions.